Becoming a totally inclusive school a guide for teachers and school leaders - Aow, Angeline; Hollins, Sadie; Whitehead, Stephen (Stephen M.) (Routledge, Taylor & Francis Group, 2023)
"Educators are at a crossroads and the global call for institutions to address their inequitable structures is ringing loudly. For teachers and school leaders who are hearing that call, this book offers knowledge and guidance for becoming a totally inclusive school. Each chapter delves into key ideas that are fundamental to addressing the complex challenge of achieving total inclusivity - one which encompasses and values racial diversity, gender equality, and LGBTQ inclusivity, neurodiversity and more. Across the three sections, the authors introduce key terms and concepts important to inclusivity, focused on mindsets, behaviours and systems and structures. They explore how interactions contribute to or impede progress, and engage with tools, stories and reflection points to translate knowledge into practice. Written in an accessible style with reflective exercises in every chapter, the book will guide educational professionals along the pathway to becoming advocates for inclusivity in their schools and communities"--